Ages, Stories, Styles - N. S. Konstantinova (Концепт: философия, религия, культура, 2023)
The contents of the next collection of the Institute of Art Studies from the series Problems of Ibero-American Art involuntarily invokes a premonition of a fascinating journey through different eras and subjects of Spanish culture: theatre, music, fine arts, social philosophy, literature of the Golden Age... The collection opens with an article by Vidas Sulinas, an expert on classical Spanish theatre. The author examines the time period from the last third of the 16th century to the beginning of the 18th century, tracing the change of three artistic styles — Renaissance, Mannerism and Baroque — using the example of the work of three classics of Spanish drama. To introduce readers to these works, the author gives brief reviews of the plots: at the heart of them is love, its mysteries, virtues and trials. The article raises a number of eternal problems of existence, including good and evil, reality and imagination and, finally, the eternally relevant motif of the artist and power. The second article written by Irina Kryazheva is devoted to the study of court musicians of Medieval Spain. The task is by no means simple, given the small number of sources. Their identification and subsequent scrupulous study are one of the undoubted advantages of the text. In the next article on percussion instruments of the Renaissance Spain, Maria Moiseeva recreates the widest palette of musical instruments of the era with their description and classification. Particular attention is paid to fruitful interaction between the European and Arab worlds. Denis Fedosov creates a voluminous canvas of church life in Catholic Spain through describing retablo as the center of artistic composition of a Spanish temple. These and other articles written by specialists make allowance for amateurs and welcome new readers. Overall, the collection turned out to be successful. First of all, due to the selection of authors. It is written professionally, which means it will be of interest to professionals, and for the same reason, along with the variety of content, it is also interesting for a wider audience.